Knowledge of sexually transmitted diseases and sexual behaviours among Gen Z in Malaysia - Muhd Irpan, Hamidah; Nordin, Enylina; Hassan, Masita; Ibrahim, Noorazilah; Hussain, Wan Shafizah (2023)
One of the world's major concerns has been the increased rates of sexually transmitted diseases (STDs) among young adults aged 15 to 24 years old. This study aimed to investigate the knowledge, attitudes, risky behaviors, and preventive practices regarding STDs among gen Z in Malaysia. A self-administered questionnaire was used for this survey. The findings revealed that the majority of them demonstrated good knowledge of STDs and had acceptable preventive practices. The marital status was found to be associated not only with their knowledge but also with their preventive practices. This study shed light on misconceptions about STDs, preventive practices, and risky behaviors, raising concerns about a potential future increase in STD incidence. Therefore, it is crucial to implement interventions that strengthen health education on STD-related issues to promote positive changes in practices, knowledge, and attitudes.